A Phytochemical Characterization and Screening Test of Simplisia and Sabrang Garlic (Eleutherine bulbosa (Mill.) Urb.) Tuber Extract - Fitri Yanti; Heni Kurniasari; Josep N. Hutahaean (Science Midwifery, 2022)
Sabrang onion (Eleutherine bulbosa (Mill.) Urb.) has been used for generations for various diseases such as breast and colon cancer, hypertension, diabetes mellitus, hypercholesterolemia and stroke. This study aims to determine the characterization and phytochemical screening of simplicia and sabrang onion bulb extract. Extracts were made by graded maceration using solvents based on their polarity levels, n-hexane, ethylacetate and ethanol as well as phytochemical screening and characterization of simplicia and extracts. The results of simplicia characterization, sabrang onion n-hexane extract (ENBS), sabrang onion ethylacetate extract (EEABS) and sabrang onion ethanol extract (EEBS) obtained water content of 8.64%, respectively; 4.98%; 8.27% and 9.11%; water soluble extract content of 8.52%; 1.12%; 9.51% and 72.19%; ethanol soluble extract content of 14.05%; 2.28%; 49.26% and 81.66%; total ash content 2.89%; 0.34%; 0.43% and 1.73% and the acid insoluble ash content is 0.59%; 0.06%; 0.07% and 0.20%. The results of the phytochemical screening of simplicia and extracts obtained groups of alkaloids, flavonoids, glycosides, saponins, anthraquinone glycosides, tannins and triterpenoids/steroids.